Enteral feeding in the critically ill: comparison between the supine and prone positions: a prospective crossover study in mechanically ventilated patients - van der Voort, Peter HJ (BioMed Central, 2001)
INTRODUCTION: Prone position is effective in mechanically ventilated patients to improve oxygenation. It is unknown if prone position affects gastric emptying and the ability of continued enteral feeding. AIM: To determine tolerance of enteral feeding by measuring gastric residual volumes in enterally fed patients during supine and prone positions. METHODS: Consecutive mechanically ventilated intensive care patients who were turned to prone position were included. All patients were studied for 6 hours in supine position, immediately followed by 6 hours in prone position, or visa versa. The rate of feeding was unchanged during the study period. Gastric residual volume was measured by suctioning the naso-gastric tube after 3 and 6 hours in the same position. Wilcoxon test and regression analysis were used for analysis. RESULTS: The median volume of administered enteral feeds was 95 ml after 6 hours in supine position and 110 ml after 6 hours in prone position (P = 0.85). In 10 patients, a greater gastric residual volume was found in prone position. In eight others a greater volume was found in supine position. In 18 of 19 patients, gastric residual volumes in both positions were ≥ 150 ml in 6 hours or ≤ 150 ml in 6 hours. Significantly more sedatives were used in prone position. Regression analysis excluded dopamine dose and the starting position as confounders. CONCLUSION: Our results suggest that enteral feeding can be continued when a patient is turned from supine to prone position or vice versa. The results indicate that patients with a clinically significant gastric residual volume in one position are likely to have a clinically significant gastric residual volume in the other position.